The Effect of Brain Exercise on Housewives' Stress Levels - Rosdiana, Yanti; Putri, Rona Sari Mahaji; Maemunah, Neni (Care : Jurnal Ilmiah Ilmu Kesehatan, 2024)
Housewives are particularly vulnerable to stress when dealing with household problems, especially when they lack adequate mental and physical preparation. Brain gym or brain exercise known for its effectiveness in reducing stress among housewives, consists of simple movements designed to stimulate, relieve, and relax the brain. This activity can help activate the brain and clear the minds of housewives. This study utilized a quasi-experimental design. The population consisted of 30 housewives living in the RT 6 RW 1 Kedung Kandang Buring area. Data were collected using the Perceived Stress Scale (PSS-10) questionnaire and analyzed with a paired sample t-test. The results showed a significant p-value of 0.000 (α 0.05), indicating that brain gym has a significant effect on reducing stress among housewives. There was a notable decrease in stress levels before and after performing brain gym. It is recommended that housewives regularly engage in brain exercise to maintain and improve their mental health condition.